2013
DOI: 10.1002/pbc.24559
|View full text |Cite
|
Sign up to set email alerts
|

Transplant‐related mortality following allogeneic hematopoeitic stem cell transplantation for pediatric acute lymphoblastic leukemia: 25‐year retrospective review

Abstract: BackgroundOver the last 25 years, donor source, conditioning, graft-versus-host disease prevention and supportive care for children undergoing hematopoeitic stem cell transplantation (HSCT) have changed dramatically. HSCT indications for acute lymphoblastic leukemia (ALL) now include high-risk patients in first and subsequent remission. There is a large burden of infectious and pre-HSCT morbidities, due to myelosuppressive therapy required for remission induction. We hypothesized that, despite these trends, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 55 publications
5
49
0
1
Order By: Relevance
“…These results are in accordance with Mateos et al 42 who found a survival gain (OS and event-free survival) due to TRM reduction in allo-SCT for pediatric ALL. Focusing on the risk status disease, 5-year OS and 5-year PFS were significantly improved in the HR group between 1983 and 1999 period and 2000 and 2010, but this was not observed in the SR group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with Mateos et al 42 who found a survival gain (OS and event-free survival) due to TRM reduction in allo-SCT for pediatric ALL. Focusing on the risk status disease, 5-year OS and 5-year PFS were significantly improved in the HR group between 1983 and 1999 period and 2000 and 2010, but this was not observed in the SR group.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in agreement with previous studies. 38,42 Relapse remained the major cause of death post allo-SCT. Therefore, therapeutic advances are needed for both a better control of the pre-transplant disease and an improved post-transplant management.…”
Section: Discussionmentioning
confidence: 99%
“…Esto coincide con estudios previos sobre la MRT. 23 La literatura aporta datos que ayudan a entender la relación entre la comorbilidad previa al TH y estos eventos. Sorror y cols., reportaron, en un estudio multicéntrico reciente, una asociación entre el ICTH y el riesgo de formas más graves de EICH, 24 lo que coincide con la tendencia observada en nuestra muestra.…”
Section: Discussionunclassified
“…This is consistent with previous studies on TRM. 23 Data obtained from the literature are useful to understand the relationship between pre-HCT comorbidities and these events. Sorror et al reported, in a recent multicenter study, an association between HCT-CI and the risk for more severe forms of GvHD, 24 consistent with the trend observed in our sample.…”
Section: Discussionmentioning
confidence: 99%